Green Synthesis of Zero Iron Nanoparticles and its Application in the Degradation of Metronidazole - Masoud Yousefi; Kourosh Rahmani; Reza Jalilzadeh Yengejeh; Sima Sabzalipour; Gholamreza Goudarzi (Shiraz University of Medical Sciences, 2021)
Background: The production and consumption of pharmaceutical compounds, including antibiotics, and their entry into the environment have raised concerns for experts. It is important to find appropriate methods for treatment of these pollutants from aquatic environments. In this study, nano-persulfate process using green synthesis of zero iron nanoparticles was used in decomposition of the antibiotic Metronidazole (MNZ). Methods: In this study, first, zero iron nanoparticles were synthesized using oak leaves. Then, the characteristics of these nanoparticles were determined using electronic images such as SEM, and TEM. In the  experimental part of the study, the effect of operating conditions such as nZVI dosage, persulfate concentration and pH of the PS/nZVI process on degradation of MNZ in aqueous solution Was examined. Results: The results of this study showed that the PS/nZVI process had an acidic nature for removal of MNZ. The optimal conditions for this process were: the dosage of nZVI was 1.8 g/l, the concentration of persulfate was 1.5 mg/l, and pH was 3 for the degradation of 50 mg/l MNZ at contact time of 90 min. The maximum MNZ removal efficiency using PS / NZVI process was about 98.4 % in these conditions. Conclusion: It can be concluded that the synthesis of green zero iron nanoparticles is an economical and environmentally friendly method that can be used to remove MNZ from aqueous solutions.